Association of outdoor air pollution and indoor renovation with early childhood ear infection in China. (February 2017) - Deng, Qihong; Lu, Chan; Jiang, Wei; Zhao, Jinping; Deng, Linjing; Xiang, Yuguang
Abstract: Background: Otitis media (OM) is a common infection in early childhood with repeated attacks that lead to long-term complications and sequelae, but its risk factors still remain unclear. Objective: To examine the risk of childhood OM for different indoor and outdoor air pollutants during different timing windows, with a purpose to identify critical windows of exposure and key components of air pollution in the development of OM. Methods: We conducted a retrospective cohort study of 1617 children aged 3–4 years in Changsha, China (2011–2012). Children's life-time prevalence of OM and exposure to indoor air pollution related to home renovation activities were surveyed by a questionnaire administered by the parents. Children's exposure to outdoor air pollution, including nitrogen dioxide (NO2 ), sulfur dioxide (SO2 ), and particulate matter with an aerodynamic diameter ≤ 10 μm (PM10 ), was estimated using the measured concentrations at municipal monitoring stations. The odds ratio (OR) and 95% confidence interval (CI) of childhood OM for prenatal and postnatal exposure to indoor and outdoor air pollution were examined by using logistic regression model. Results: Life-time prevalence of OM in preschool children (7.3%) was associated not only with prenatal exposure to industrial air pollutant with adjusted OR (95% CI) = 1.44 (1.09–1.88) for a 27 μg/m 3 increase in SO2 but also with postnatal exposure to indoor renovations with OR (95% CI) = 1.62 (1.05–2.49) for new furniture and 1.81 (1.12–2.91) for redecoration, particularly in girls. Combined exposure to outdoor SO2 and indoor renovation significantly increased OM risk. Furthermore, we found that exposure to outdoor SO2 and indoor renovation were significantly associated with the onset but not repeated attacks of OM. Conclusion: Prenatal exposure to outdoor industrial air pollution and postnatal exposure to indoor renovation are independently associated with early childhood OM in China and may cause the OM onset. Graphical abstract: Highlights: ● Otitis media (OM) is a common infection in children but its risk factors still remain unclear. ● We examined key air pollutants and critical exposure windows in the development of OM. ● Both outdoor and indoor air pollutants were significantly associated with OM onset. ● Prenatal outdoor exposure and postnatal indoor exposure were associated with childhood OM. ● Combined exposure to indoor and outdoor air pollution significantly increased OM risk.